Pengaruh Pola Pendidikan Kuttab terhadap Pembentukan Karakter Siswa di Pondok Pesantren Darussalamah Al-Mubarok Cianjur - Marsha Affifah Amani; Iman Saifullah; Anton Anton (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Amidst high rates of bullying and suboptimal student character indices, character education remains a critical challenge. This study aims to evaluate the effectiveness of the Kuttab educational method as a systemic model for building student character at the Darussalamah Al-Mubarok Islamic Boarding School, Cianjur. This research investigates the relationship between the Kuttab educational pattern and the internalization of student character. Utilizing a quantitative approach, the study employs simple linear regression analysis on 31 respondents. The results of the analysis indicate that the Kuttab educational pattern functions as a systematic stimulus that exerts a positive and significant influence on character development. This model effectively serves as a filter and moral control mechanism to protect students from negative environmental influences. Success in forming a robust moral identity relies on integrating methods of exemplary role modeling (uswah hasanah) and habituation (al-adah) based on faith (iman) and etiquette (adab). The findings demonstrate that the Kuttab pattern serves as a strategic reference for building a more comprehensive and measurable model of character education. Furthermore, the study emphasizes the importance of synergy between the Islamic boarding school environment, families, and social media in ensuring the sustainability of character education.